Retinal progenitor cells (jCell) for retinitis pigmentosa - Yang, Jing; Kuppermann, Baruch D.; Liao, David; Mehta, Mitul C.; Hsiang, Chinhui; Menges, Steven; Boyer, David S.; Klassen, Henry (Frontiers in Cellular Neuroscience, 2025)
ObjectiveTo assess the safety and tolerability of intravitreal injection of human retinal progenitor cells (RPCs) at multiple dose levels in adults with non-syndromic retinitis pigmentosa (RP).DesignA prospective, multicenter, open-label, single-arm, Phase I/IIa safety study of RPCs in adults with RP (n = 28). Two patient cohorts were studied: Cohort 1: BCVA no better than 20/200 and no worse than Hand Motions, and Cohort 2: BCVA no better than 20/40 and no worse than 20/200).SubjectsAdults (n = 28) with a clinical diagnosis of RP confirmed by electroretinogram, consenting to gene mutation typing for genes involved in inherited retinal degenerations and related disorders, and willing to undergo human leukocyte antigen (HLA) typing.MethodsSubjects, who were not selected for genotype, were divided across the two vision cohorts with each receiving a single intravitreal injection of one of: 0.5, 1.0, 2.0, or 3.0 × 106 allogeneic RPCs. Initially, subjects received the lowest dose (0.5 × 106 RPCs) in the worse-seeing eye. Each dose group contained equal numbers of subjects from Cohorts 1 and 2.ResultsIntravitreal RPC injection was well tolerated and associated with mostly transient mild to moderate adverse events. There were no signs of graft rejection. While primarily a safety study, exploratory efficacy assessments suggested improved BCVA measurements at all doses, with a possible dose-response at the highest levels. Mean BCVA change from pre-treatment to Month 12 in the treated vs untreated eyes was 1.4 letters for the 0.5 × 106 dose group, 1.0 letters for the 1.0 × 106 group, 4.8 letters for the 2.0 × 106 group, and 9.0 letters for the 3.0 × 106 group. Additional patient-reported changes included increased light sensitivity, improved object recognition, color discrimination, and reading.ConclusionA single intravitreal injection of RPCs was well tolerated in this safety study. The exploratory efficacy data suggest potential improvement of BCVA in some RP patients, particularly at the highest dose. While viewed cautiously, the possible treatment effect should be further investigated in larger controlled studies. The RPC technology has received FDA Regenerative Medicine Advanced Therapy designation. Later phase studies are ongoing.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT02320812, NCT02320812.